2014
DOI: 10.3109/10826084.2014.901386
|View full text |Cite
|
Sign up to set email alerts
|

Improving Understanding of the Quitting Process: Psychological Predictors of Quit Attempts Versus Smoking Cessation Maintenance among College Students

Abstract: This study examined motivation, positive and negative outcome expectations of quitting, and self-efficacy as predictors of quit attempts and cessation maintenance in a smoking cessation intervention for college students (N = 303). Psychological measures assessed at baseline were used to predict smoking behavior outcomes. Analysis of Variance (ANOVA) and logistic regression analysis revealed that motivation and self-efficacy were strong, differential predictors of quit attempts and cessation maintenance, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Motivation and confidence to quit were measured on 1–10 scales, asking participants “On a scale from 0 to 10, how motivated/confident are you to quit smoking?” These items have been shown to be sensitive to baseline levels of interest in quitting prior to treatment, and to relate to cessation outcomes in both adults and college students (4042). We also assessed the reported number of quit attempts in the previous year and established stage of change for quitting (33) by asking participants about their intention to quit in the next 6 months and 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Motivation and confidence to quit were measured on 1–10 scales, asking participants “On a scale from 0 to 10, how motivated/confident are you to quit smoking?” These items have been shown to be sensitive to baseline levels of interest in quitting prior to treatment, and to relate to cessation outcomes in both adults and college students (4042). We also assessed the reported number of quit attempts in the previous year and established stage of change for quitting (33) by asking participants about their intention to quit in the next 6 months and 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of higher levels of self-efficacy-- one’s belief in one’s ability to perform a specific behavior in a given situation (Bandura, 1977)--has been demonstrated in weight loss (Armitage et al, 2014), exercise (Cramer et al, 2014), smoking cessation (Lee et al, 2014), antiretroviral medication adherence (Tyer-Viola et al, 2014), contraception use (French and Holland, 2013), and reduction of alcohol use (Foster et al, 2014). Drinking-related self-efficacy in particular- that is, self-efficacy to reduce or resist drinking in particular situations-has often been studied in order to explain changes in drinking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Existing measures of quitting expectancies have been shown to have adequate internal and concurrent validity (Dijkstra et al, 1996; Hendricks et al, 2009; Sirota et al, 2010; Kale et al, 2015; Abrams et al, 2011; Hendricks et al, 2011; Kahler et al, 2013; Eklund et al, 1997; Lee et al, 2014; Macnee & Talsma, 1995; McKee et al, 2005; Rohsenow et al, 2015). The internal and concurrent validity of the PRBQ in our study appears to be similar to or slightly higher than that of these other measures.…”
Section: Discussionmentioning
confidence: 99%
“…Only one advantage (more energy and alertness) and one disadvantage (loss of concentration) predicted future quit attempts, and none of the items predicted abstinence success among attempters (Kale et al, 2015). Another study of smokers not trying to quit found negative expectancies about abstinence predicted a quit attempt but not abstinence, and that positive expectancies predicted neither (Lee et al, 2014). A human laboratory study found abstinence expectancies predicted greater withdrawal symptoms, but did not examine quit attempts or abstinence (Hendricks & Leventhal, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation